Kindler Syndrome - Masood Qazi; Manzoor Sheikh; Majid Imran (Wolters Kluwer Medknow Publications, 2000)
Kindler syndrome is a rare genodermatosis characterized by acral blistering since early infancy, photosensitivity and progressive poikiloderma of the extremities. This syndrome in a 12 years old female with history with of consanguinity among parents is being reported for it rarity.